Influence of Emojis on Online Trust Among College Students - Zhang, Mei; Ding, Shuheng; Liu, Yining; Li, Hailong; Zhu, Yanchun; Qin, Chunlei (Frontiers in Psychology, 2021)
Emojis are increasingly used in online communication and expression, however, most previous studies have focused on describing this phenomenon, but less on how it affects interpersonal trust relationships. Therefore, this study examines the effect of emojis on online interpersonal trust among college students through three experiments. A total of 62 college students were recruited for Experiment 1. The results demonstrated that positive emoji (<inline-graphic xlink:href="fpsyg-12-747925-i001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />) improved the level of trust of trustors in the trust game [t(60) = –2.79, p = 0.007], whereas that of the control group exerted no effect on the initial level of online trust among college students. Then, 74 college students were selected for Experiment 2. The results indicated no significant differences between the experiment and control groups in terms of the influence of negative emojis (<inline-graphic xlink:href="fpsyg-12-747925-i002.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />) on initial online trust using. A joint analysis (via ANOVA) of Experiments 1 and 2 illustrated that the type of emoji exerted a significant effect [F(2,96) = 3.96, p = 0.02, η2 = 0.08] on college students’ online trust. Finally, we recruited 111 participants for Experiment 3 to explore the role of emojis on online trust among acquaintances. The results suggested that the individual propensity to trust plays a moderate role in the relationship between emojis and online trust among acquaintances. That is, emojis influenced interpersonal trust among acquaintances only if the level of propensity to trust, is low.